In retrospect: intensivists and COVID-19 pandemic on day zero. An analysis of communication exchanges on WhatsApp - Hamui Sutton, Liz (2024)
Objective: To describe and analyze, at various levels, the communication exchanges that took place in a group chat of intensivists using the instant messaging application WhatsApp during the first stage of the COVID-19 pandemic, specifically on the day the first case was confirmed in Mexico. An intense situation showing the three dimensions of the theoretical framework is stood out. Materials and methods: A qualitative research of WhatsApp messages shared between 239 intensivists at the beginning of the pandemic, specifically throughout February 27, 2020. A narrative analysis was used to interpret a fragment of a chat. A schema with three dimensions (analysis of shared information, standards of social action in COVID-19 patient care and emotional expressions) was developed to code and classify the messages. Results: The communication exchanges via WhatsApp made it possible to give meaning to the emerging knowledge about COVID-19 in the narrative plots. They also influenced the implementation of appropriate actions in hospital environments and helped modulate emotions in front of the pandemic. In addition, it fostered bonds of solidarity and empathy between intensivists to face personal and social suffering with resilience. Conclusions: The chat messages reflected human relationships and the deep concerns of people in crisis situations. The study provided insight into the forms and meanings of communication exchanges with the use of technological devices in times of crisis to guide the implementation of actions in emerging situations such as the COVID-19 pandemic. WhatsApp responded to the need for information, with scientific and truthful data, about the pandemic. It was noted that intensivists benefited from instant messaging by cooperating in critical situations and experiences within the context of an evolving health crisis.